Politics and Corporate Content: Situating Corporate Strategic Communication between Marketing and Activism. Issue 5 (19th October 2020) - Hill, Stephanie
ABSTRACT: While it has historically been seen as a strategic risk or error for companies to get involved in contentious politics, new data on consumers, efforts to personalize marketing, and growing interest in corporate social responsibility have made activist and political content a significant part of public relations for many companies. The ability to communicate different messages in targeted ways online has perhaps facilitated corporate political advocacy by creating new opportunities to engage the public. These practices are seen by many organizations as an opportunity to build relationships with consumers, but they may present new challenges for political bodies and the public. This research investigates the commercial backlash to a contentious piece of legislation in North Carolina and considers the implications of the incorporation of political content into commercial communication. To do this, it examines how companies involved in the controversy integrated messages about the legislation into their public channels. Using the typologies of corporate involvement created, this article reflects on the role played by businesses in the case study, the strategic goals served by their involvement, the likelihood of seeing similar involvement by for-profit organisations in different circumstances, and the significance of corporate political advocacy on public engagement with civic and political issues.